Using the Community of Inquiry framework to analyze emojis as an emerging language in an online educational experience via WhatsApp - Braga, Junia; Gunter, Glenda; Reeves, Jennifer; Racilan, Marcos (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2023)
With the ever-growing interest in WhatsApp as a social space to accommodate pedagogical initiatives, the role of emojis as an emergent Internet language in this social space needs to be better understood as mobile technologies have been integrated in education. With that in mind, this paper reports a study that employed an embedded correlational mixed methods design, and aimed to identify: the emojis used to support cognitive, teaching, and social presences in a teacher education course via WhatsApp; participants’ attitudes regarding the use of emojis, and their age and gender relation to this use. The data generated from the interactions of the teachers via WhatsApp were analyzed and discussed based on Garrison et al.’s (1999) Community of Inquiry Model. This conceptual framework identifies crucial elements for successful online educational experiences and assumes learning occurs through the interaction of three core elements: social, cognitive and teaching presences. The findings show that emojis can effectively be used to support teaching, cognitive, and social presences. The high frequency of emojis seem to be both culturally situated and gender related.